Nutrient metabolism in regulating intestinal stem cell homeostasis - Ruicheng Shi; Bo Wang (2024)
Intestinal stem cells (ISCs) are known for their remarkable proliferative capacity, making them one of the most active cell populations in the body. However, a high turnover rate of intestinal epithelium raises the likelihood of dysregulated homeostasis, which is known to cause various diseases, including cancer. Maintaining precise control over the homeostasis of ISCs is crucial to preserve the intestinal epithelium's integrity during homeostasis or stressed conditions. Recent research has indicated that nutrients and metabolic pathways can extensively modulate the fate of ISCs. This review will explore recent findings concerning the influence of various nutrients, including lipids, carbohydrates, and vitamin D, on the delicate balance between ISC proliferation and differentiation.